Nutritional Status of Tuberculosis Patients in Against Serum Glutamate Pyruvate Transaminase Levels - Widagdo, Iqbal Donarika; Setyoko, Setyoko; Setiawan, M. Riza (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2016)
Background: Treatment of Tuberculosis patients are given in the form of a drugs combination. Some drugs which are Pyrazinamide, Isoniazid and Rifampicin can provide hepatotoxic side effects. Specific sign of hepatotoxic occurrence is increasing in the Serum Glutamate Pyruvate Transaminase levels. One of factors that influence hepatotoxicity is nutritional status. This study aims to determine the relationship between nutritional status and levels of Serum Glutamate Pyruvate Transaminase in tuberculosis patients.Methods: A non-experimental correlation study, retrospective approach with total sampling method, according to inclusion and exclusion criteria. Located at tCommunity Lung Health Center (BKPM) Ambarawa area. The analysis used the Spearman rank correlation testResults: Based on the test results of Spearman Rank correlation test, the correlation coefficient (r) is  -0.267. Hypothesis test results also showed 0.037 (p-value <0.05), which means the existence of a significant correlation between variabels.Conclusion: There is a relationship between nutritional status and levels of Serum Glutamate Pyruvate Transaminase in tuberculosis patients.